Adsorption of fluoride ions by Zn-Al layered double hydroxides - Mandal, Sujata; Mayadevi, S. (Applied Clay Science, 2008)
Zn-Al layered double hydroxides (LDHs) with different molar ratios Zn/Al (0, 0.17, 0.34, 0.97, 3.47, proportional to) were prepared by the co-precipitation of chlorides, characterized and evaluated for their fluoride adsorption at room temperature from aqueous solutions. The fluoride adsorption of the as-synthesized LDHs was influenced by the chemical composition of the LDHs and ZA-11 (Zn/Al = 0.97) had the highest capacity for fluoride adsorption (1.14-4.16 mg/g). The adsorption increased after calcination of the LDH up to 500 degrees C. The equilibrium data were fitted to the Freundlich, Langmuir, and Temkin equations. The kinetics of fluoride adsorption followed the pseudo-second order model. (C) 2007 Elsevier B.V All rights reserved.
Keywords: Adsorption; Anionic clay; Fluoride; Layered double hydroxide

Adsorption of aqueous selenite [Se(IV)] species on synthetic layered double hydroxide materials - Mandal, Sujata; Mayadevi, S.; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2009)
{Layered double hydroxide materials (Zn/Al, Mg/Al, Zn/Fe) with varying composition (M(2+):M(3+) molar ratio

Azoic dye hosted in layered double hydroxide: physicochemical characterization of the intercalated materials - Mandal, Sujata; Tichit, Didier; Lerner, Dan A.; Marcotte, Nathalie (Langmuir, 2009)
Intercalation compounds were obtained by introduction of guest methyl orange (MO) into the interlayer space of host Mg/Al and Ni/Al layered double hydroxides (LDHs). Three synthesis methods of organic anion-LDH intercalation compounds, i.e., coprecipitation, reconstruction of the M(II)(Al)O mixed oxides, and anion exchange of LDH were compared. The former Method gives rise to a highly organized MO-intercalated Mg/Al LDH with an interlayer spacing of 2.43 rim and up to seven (001) reflection orders. Reconstruction or the mixed oxide by intercalation with MO in the restored LDH was only achieved with Mg(Al)O. In this case. a competitive adsorption of MO on the external Surface Of the crystals was also seen. On the other hand, intercalation compounds exhibiting interlayer spacing of 2.43 run were obtained with both Mg- and Ni-containing LDH using the anionic exchange method. The equilibrium and kinetic adsorption properties of the compounds were analyzed by UV-visible spectroscopy in anionic exchange experiments. According to the pseudo-second-order adsorption model, the amounts of adsorbed MO reach 3.82 and 2.83 mequiv/g for Mg- and Ni-containing LDHs, respectively, which are close to their respective anionic exchange capacity. The adsorption rates are on the same order of magnitude for the two LDHs (0.10-0.44 g mmol(-1) min(-1)), the equilibrium being reached in less than 60 min. The decomposition of MO by combustion of the organic moieties under an oxidizing atmosphere is delayed in Mg-containing MO-LDH hybrids when compared to the free MO molecule, showing that the thermal stability of MO species is enhanced after intercalation. In Ni-containing LDH, the main decomposition step of MO occurs 300 degrees C below that of Mg-containing LDH. This was rationalized in terms of a catalysis by the Ni-containing oxides formed during the thermal treatment. So these materials exhibit several advantage useful for the development of eco-friendly processes for the removal Of dyes from effluents of textile, plastic, and paper industries.

Adsorption of cresols on zinc-aluminium hydroxides - a comparison with zeolite-X - Vijayakumar, J.; Chikkala, Suresh K.; Mandal, Sujata; Mayadevi, S. (Separation Science and Technology, 2011)
Liquid phase adsorption of m-cresol on Zn-Al hydroxide adsorbents with three different Zn/Al molar ratios was studied in different solvents and compared with commercial zeolite 13X. Among the three adsorbents, ZA-16 showed adsorption capacity similar to commercial zeolite 13X. Solvents used for the preparation of m-cresol solution were found to influence the adsorption capacity. The adsorption capacity was maximum for the solution of m-cresol in n-hexane. Conventional Langmuir and Freundlich adsorption isotherm equations were used to explain the adsorption behavior. The kinetics of m-cresol adsorption followed the first-order Lagergren kinetic model. p-Cresol/m-cresol separation factor was the highest when toluene was used as the organic medium.
Keywords: Adsorption; cresol; zeolite; zinc-aluminium hydroxide

Alginate and hydrotalcite-like anionic clay composite systems: synthesis, characterization and application studies - Mandal, Sujata; Patil, Varsha S.; Mayadevi, S. (Microporous and Mesoporous Materials, 2012)
Hydrotalcite-like anionic clays (Zn/Al and Mg/Al) were intercalated with sodium alginate to form organic-inorganic composite adsorbents for water treatment applications. The synthesized composites were characterized using different characterization techniques viz. XRD, DRIFTS, SEM and surface area/porosity analysis. The adsorption potential of the alginate-clay composites was examined for removal of fluoride ions and Orange II dye from water by adsorption. Our studies revealed that these composites had high adsorption capacity for the adsorption of fluoride and Orange II dye from aqueous solutions. The adsorption capacity of the composites was considerably higher than that of either alginate or clay, used individually. The results indicated that these materials might be useful sorbents for groundwater purification/effluent treatment. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Alginate; Anionic clay; Composite; Fluoride; Orange II dye